Investigating efficiency droop in InGaN/GaN quantum well structures using ultrafast time‐resolved terahertz and photoluminescence spectroscopy. Issue 5 (3rd February 2016) - Dunn, Aniela; Spencer, Ben F.; Hardman, Samantha J. O.; Graham, Darren M.; Hammersley, Simon; Davies, Matthew J.; Dawson, Phil; Kappers, Menno J.; Oliver, Rachel A.; Humphreys, Colin J.
Abstract: The mechanisms governing efficiency droop in an In0.18 Ga0.82 N/GaN multiple quantum well structure were investigated using a combination of ultrafast time‐resolved terahertz and photoluminescence spectroscopy. From excitation fluence dependent studies, a reduction in the room temperature photoluminescence efficiency to 3% of its maximum value was observed for an excitation fluence of 0.96 mJcm ‐2 . A correlation was found between the onset of efficiency droop and the emergence of a peak on the high‐energy side of the quantum well emission with a 1/ e decay time of 19.6 ps. These characteristics were attributed to the saturation of localised states and the population of higher energy delocalised states. Time‐resolved studies revealed different scaling behaviours between the terahertz and photoluminescence decay dynamics, suggesting that the saturation of localised hole states may be playing a part in the onset of efficiency droop. (© 2016 The Authors. Phys. Status Solidi C published by WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)